Validación de ensayo de trazadores a partir de un modelo CFD para un reactor ASTBR a escala laboratorio (2021)
The present work focuses on the simulation of a tracer test already carried out experimentally in an anaerobic structured bed reactor (ASTBR) and on its respective validation by means of the open source software OpenFoam. In the first instance, a bibliographic review of articles related to the experimental design of the reactor and the CFD methodology was made, obtaining as a result, the dimensions, capacity of the reactor and the most important aspects for the development of the CFD methodology (speed field ). Additionally, an approach was made to the simpleFoam and pisoFoam solvers available in OpenFoam.